CULTURAL TRANSLATION OF PROVERBS FROM NEPALI INTO ENGLISH - Neupane, Nabaraj (LLT Journal: A Journal on Language and Language Teaching, 2021)
Proverbs are witty, pithy, and epigrammatic expressions. They are idiosyncratic, being based on a specific culture. As cultural translation is difficult, translation of proverbs is not easy. Yet, translation practices on such genre have been appearing. In such a scenario, some such practices are found in the domain of Nepali into English translations. In this background, the present study aims at reviewing the available models for translating proverbs and recommending one, which can be used for translating Nepali proverbs into English. To achieve the objectives, I collected twenty proverbs purposively from Lall (1991) and Sharma (2000), primarily because I could deal only with twenty in a short period and limited space. By way of qualitative analysis and interpretation and by testing Wilson's (2009) model, I have concluded that the model is applicable for the purpose.